IMPLEMENTASI MANAJEMEN LAYANAN DALAM PENDIDIKAN ISLAM - Prastyawan Prastyawan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
Islamic education must be managed as good as possible. Management of Islamic education is one of the efforts to increase the quality of life of the people (ummah) from backwardness morally, materially, and spiritually. In service management, managers should strive to provide the best service to all customers by moving all the management and staff to give satisfaction to all parties through a variety of ways. By doing so, the manager of Islamic education is demanded to provide satisfaction to both internal and external customers. Both of these customers have a reciprocal relationship and mutual need: internal customers require external ones, and vice versa. When internal customers are served well, then they are satisfied, then the service they received will be a factor of professional attitudes in working, such as trying to improve performance, increasing loyalty, improving discipline, and so on. If the external customers are also served well and they feel satisfied, there will be a high confidence in the existence of the institution, even they will provide real support.